A critical review of mineral substrates used as filter media in subsurface constructed wetlands: costs as a selection criterion. Issue 1 (31st December 2023) - Sandoval Herazo, Luis Carlos; Alvardo-Lassman, Alejandro; Marín-Muñiz, José Luis; Rodríguez-Miranda, Juan Pablo; Fernández-Lambert, Gregorio
ABSTRACT: This study reports a literature review of the state of the art, 2000-2020, on the substrates that are used as support media in constructed wetlands with subsurface flow. Its importance compared to the most used substrates worldwide and its economic feasibility as a substrate in CW. 13 different types of substrates have been identified in 155 different studies, but the most used substrates were gravel (32%) and sand (23%) for the development of bacterial associations. However, gravel and sand used in full-scale CW are expensive (10–35 $USD/m 3 ), for wastewater treatment in small communities with economic difficulties. The tendency is to use substrates such as gravel (32%), sand (23%), sediments (13%), limestone or river rock (11%), granite (8%), zeolite (6%) and other alternative materials (7%). Among these we can mention: ceramics, pumice, steel, bricks, shells of different local aquatic fauna and some stone materials easily found in the study area. Therefore, the development of substrates of lower commercial value, reused material and material of easy operation is important, especially in developing countries where economic resources are one of the main constraints in the implementation of wastewater treatment systems. The use of treatment wetlands with economic materials detected in this study indicate that the future in wastewater treatment is this technology, because present multiple objectives, which include water treatment, fertilizer production, enhancement of biodiversity and cooling, vegetation production for handicraft, etc. CW are a technology with future role in circular economy that want to respond to sanitation worldwide. GRAPHICAL ABSTRACT: UF0001